MODEL MATEMATIKA GERAK PENDULUM DENGAN MEMPERTIMBANGKAN GAYA GESEK UDARA - Rukmono Budi Utomo (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2016)
This paper aims to construct a mathematical model of the pendulum motion by considering the frictional force of air. The study was conducted by first making a pendulum motion illustration with a length of rope and pendulum mass vertically that given deviation and speed. Based on that created a mathematical model of motion of the pendulum and its determination to find out the time it takes the pendulum passing through the zero point and the current time there is no change in the speed deviation of the pendulum. In this study will also be given a simulation of mathematical models that have been made.